The Scientific Rigor of the Objective Structured Examination for Competency Assessment in Health Sciences Education: A Systematic Review. - Pelland, Lucie; Kolomitro, Klodiana; Hopkins-Rosseel, Diana; Durando, Paola (Journal of Physical Therapy Education (Lippincott Williams & Wilkins), 2022)
Supplemental Digital Content is Available in the Text. Background and Purpose.: The objective structured clinical examination (OSCE) is widely used as an assessment of competency in health sciences education. The aim of our systematic review was to appraise the scientific rigor of the OSCE as a competency-based assessment in health sciences education, including physical therapy. Methods.: Our search was performed in 6 databases—Ovid MEDLINE(R), CINAHL, EMBASE, APA PsycINFO, ERIC, and Web of Science—to identify original data evaluating the OSCE in programs of education in physical therapy and related health sciences disciplines. Data were extracted as per the Utility Model to evaluate the validity, educational impact, reliability, acceptability, and costs of the OSCE in these programs. Results.: The search identified 106 records, with 13 studies meeting our eligibility criteria. The OSCE is distinct from traditional clinical assessments, with low-to-fair concurrent validity between the 2 assessment types. The OSCE was used for instructional design, namely, curriculum development and alignment, and for educational practice, namely, making decisions on students' readiness for practice. Limitations of the OSCE include poor-to-low validity to predict practice readiness and low-to-acceptable reliability, with student-specific, domain-specific, and examiner-specific effects on outcomes identified. Strategies were provided which could improve the scientific rigor of the OSCE. Discussion and Conclusion.: Based on current evidence, the scientific rigor of the OSCE may be insufficient to support its use to make academic decisions on students' standing in health sciences programs, including physical therapy, and readiness for clinical practice, with confidence. However, the OSCE can play an important role in instructional design and in guiding student learning. Protocol registration: PROSPERO, ID 162338.